2008
DOI: 10.1158/0008-5472.can-07-2668
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cell–Secreted Caveolin-1 Has Proangiogenic Activities in Prostate Cancer

Abstract: Caveolin, a major structural component of specialized plasma membrane invaginations (caveolae) that participate in diverse cellular activities, has been implicated in the pathogenesis of several human diseases, including cancer. We showed in earlier studies that caveolin-1 (cav-1) is consistently and strongly overexpressed in metastatic prostate cancer and is secreted in a biologically active form by virulent prostate cancer cells. Using both in vitro and in vivo model systems, we now present evidence supporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
92
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 78 publications
(99 citation statements)
references
References 35 publications
7
92
0
Order By: Relevance
“…There is accumulating evidence that overexpression of Cav promotes tumor growth and metastasis of prostate cancer via diverse pathways (3)(4)(5)(6), while PEDF may protect against the progression of prostate cancer, via anti-angiogenic, anti-inflammatory and proapoptotic effects (17)(18)(19). To the best of our knowledge, the present study demonstrated for the first time that treatment with 1 or 10 nM PEDF significantly inhibited the Cav-induced increase in IL-8 mRNA expression in PC-3 (17).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…There is accumulating evidence that overexpression of Cav promotes tumor growth and metastasis of prostate cancer via diverse pathways (3)(4)(5)(6), while PEDF may protect against the progression of prostate cancer, via anti-angiogenic, anti-inflammatory and proapoptotic effects (17)(18)(19). To the best of our knowledge, the present study demonstrated for the first time that treatment with 1 or 10 nM PEDF significantly inhibited the Cav-induced increase in IL-8 mRNA expression in PC-3 (17).…”
Section: Discussionsupporting
confidence: 54%
“…Recently, Cav has been shown to be overexpressed in prostate cancer, and to promote the growth and metastasis of this tumor (3)(4)(5)(6). Cav has been demonstrated to activate oncogenic pathways involving Akt and to promote the proliferation of prostate cancer, in addition to stimulating tumor-associated angiogenesis and inflammation (3)(4)(5)(6). Furthermore, in a large population study involving men with a serum prostate-specific antigen of >10 ng/ml, high pre-treatment serum levels of Cav were a prognostic marker for prostate cancer recurrence (7).…”
Section: Introductionmentioning
confidence: 99%
“…14 ) or using the caveolin-1 scaffolding domain peptide (CSD, amino acids 82–101 of caveolin-1). CSD enters cells 34,35 and acts as a surrogate for full-length caveolin-1 by inhibiting kinases. 20,36 CSD inhibits all of the profibrotic cellular functions associated with low caveolin-1 (collagen overexpression by myofibroblasts, monocyte hypermigration, monocyte differentiation into myofibroblasts) as well as inhibiting tissue fibrosis in mouse skin and lung 25,27,29,30,37,38 and heart, 31,32 where CSD reduced the number of M2 macrophages in an MI model and decreased collagen accumulation in a cryoinjury model.…”
mentioning
confidence: 99%
“…Intriguingly, although caveolin-1 is predominately a membrane protein, aggressive prostate cancer cell lines have been shown to secrete biologically active caveolin-1 (8). Furthermore, secreted caveolin-1 stimulates cell growth and angiogenesis in tumor models (8,9). Serum caveolin-1 has been detected in recurrent prostate cancer after radical prostatectomy and has been proposed to be a marker for disease recurrence (8,10).…”
mentioning
confidence: 99%